2017
DOI: 10.3390/nu9020139
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Vitamin D Levels and Sleep Disturbance in Hemodialysis Patients

Abstract: Sleep disturbance is a frequent and serious complication of hemodialysis (HD). Low serum vitamin D levels have been associated with sleep quality in non-HD subjects. Our aim was to examine the possible association between serum vitamin D levels and the presence of sleep disturbance in HD patients. We recruited 141 HD patients at the HD center of the First Affiliated Hospital of Jiaxing University during 2014–2015. Serum levels of 25-hydroxyvitamin D (25(OH)D) were determined by the competitive protein-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…Evidences are growing that hyperphosphatemia was associated with poor sleep quality [ 20 , 21 , 92 , 93 ], despite inconsistencies existing [ 24 ]. While the presence of hyperphosphatemia-related pruritus could be the mediating factor for poor sleep quality [ 20 ], to the best of our knowledge, there is no clear mechanism of how poor sleep quality may influence serum phosphate level among the dialysis population.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences are growing that hyperphosphatemia was associated with poor sleep quality [ 20 , 21 , 92 , 93 ], despite inconsistencies existing [ 24 ]. While the presence of hyperphosphatemia-related pruritus could be the mediating factor for poor sleep quality [ 20 ], to the best of our knowledge, there is no clear mechanism of how poor sleep quality may influence serum phosphate level among the dialysis population.…”
Section: Discussionmentioning
confidence: 99%
“…Our study evaluated 1563 relevant literatures, but only 25 studies met the inclusion criteria, which contained a total of 3,603 subjects (Balaban et al., 2012; Bozkurt et al., 2012; Celik et al., 2015; Cikrikcioglu et al., 2016; Erden et al., 2014; Ghaderi et al., 2017; Gong et al., 2018; Gunduz et al., 2016; Han, Zhu, Shi, Wu, & Gu, 2017; Huang, Shah, Long, Crankshaw, & Tangpricha, 2013; Huzmeli, 2018; Kerley et al., 2016; Liguori et al., 2015; Majid et al., 2018; Mason et al., 2016; Mete et al., 2013; Neves et al., 2017; Pazarli, Ekiz, & Inonu Koseoglu, 2019; Qiao et al., 2018; Terzi & Yilmaz, 2016; Toujani et al., 2017; Uygur, Baki, Tanriverdi, Ornek, & Atalay, 2016; Wali et al., 2018; Zhao et al., 2017; Zicari et al., 2016). These 25 articles included 21 papers analyzing differences in vitamin D concentrations between sleep disorders and controls (Balaban et al., 2012; Bozkurt et al., 2012; Celik et al., 2015; Cikrikcioglu et al., 2016; Erden et al., 2014; Gong et al., 2018; Gunduz et al., 2016; Han et al., 2017; Huzmeli, 2018; Kerley et al., 2016; Liguori et al., 2015; Mete et al., 2013; Neves et al., 2017; Pazarli et al., 2019; Qiao et al., 2018; Terzi & Yilmaz, 2016; Toujani et al., 2017; Uygur et al., 2016; Wali et al., 2018; Zhao et al., 2017; Zicari et al., 2016) and 4 papers (RCTs) evaluating the change in the PSQI score in response to supplementation with vitamin D (Ghaderi et al., 2017; Huang et al., 2013; Majid et al., 2018; Mason et al., 2016). The detailed outcomes are presente...…”
Section: Resultsmentioning
confidence: 99%
“…For the 21 papers analyzing differences in vitamin D levels, 11 studies were conducted in Eurasia (Balaban et al., 2012; Bozkurt et al., 2012; Celik et al., 2015; Cikrikcioglu et al., 2016; Erden et al., 2014; Gunduz et al., 2016; Huzmeli, 2018; Mete et al., 2013; Pazarli et al., 2019; Terzi & Yilmaz, 2016; Uygur et al., 2016), 3 studies were performed in Europe (Kerley et al., 2016; Liguori et al., 2015; Zicari et al., 2016), and 5 studies were performed in Asia (Gong et al., 2018; Han et al., 2017; Qiao et al., 2018; Wali et al., 2018; Zhao et al., 2017) (the America group and Africa group were not analyzed because only 1 paper was included, respectively (Neves et al., 2017; Toujani et al., 2017)). Seven studies used EI to analyze the vitamin D levels (Balaban et al., 2012; Celik et al., 2015; Cikrikcioglu et al., 2016; Gong et al., 2018; Mete et al., 2013; Qiao et al., 2018; Zhao et al., 2017), and 6 studies used CI (Erden et al., 2014; Kerley et al., 2016; Neves et al., 2017; Pazarli et al., 2019; Uygur et al., 2016; Zicari et al., 2016), while the remaining studies (Bozkurt et al., 2012; Gunduz et al., 2016; Terzi & Yilmaz, 2016; Toujani et al., 2017) ( n = 4)used other methods (4 studies (Han et al., 2017; Huzmeli, 2018; Liguori et al., 2015; Wali et al., 2018) did not provide an assay method). The type of sleep disorder was OSAS (mild) in 5 studies (Bozkurt et al., 2012; Kerley et al., 2016; Mete et al., 2013; Pazarli et al., 2019; Uygur et al., 2016), OSAS (moderate) in 7 studies (Bozkurt et al., 2012; Erden et al., 2014; Kerley et al.,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with haemodialysis, sleep impairment would decrease the quality of life and increase medication use and mortality rate (Elder et al, 2008). A recent study reported that poor sleep quality is associated with lower vitamin D levels (Han et al, 2017). Disturbed sleep also causes increased mortality rates, exacerbations and use of emergency department for chronic obstructive pulmonary disease (Omachi et al, 2012).…”
mentioning
confidence: 99%